2014
DOI: 10.3389/fpsyg.2014.01477
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in event-related potentials and attentional biases to emotional facial stimuli

Abstract: Attentional processes play an important role in the processing of emotional information. Previous research reported attentional biases during stimulus processing in anxiety and depression. However, sex differences in the processing of emotional stimuli and higher prevalence rates of anxiety disorders among women, compared to men, suggest that attentional biases may also differ between the two sexes. The present study used a modified version of the dot probe task with happy, angry, and neutral facial stimuli to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…Moreover, women showed vigilance for happy faces, whereas men showed avoidance of happy faces. In another dot-probe study a gender difference was not found on the behavioral level, yet women expressed an enhanced P1 amplitude in response to the probe as compared to men, in particular for happy faces (Pfabigan, Lamplmayr-Kragl, Pintzinger, Sailer, & Tran, 2014).…”
Section: Subjectsmentioning
confidence: 84%
“…Moreover, women showed vigilance for happy faces, whereas men showed avoidance of happy faces. In another dot-probe study a gender difference was not found on the behavioral level, yet women expressed an enhanced P1 amplitude in response to the probe as compared to men, in particular for happy faces (Pfabigan, Lamplmayr-Kragl, Pintzinger, Sailer, & Tran, 2014).…”
Section: Subjectsmentioning
confidence: 84%
“…While Tran et al [54] found no attentional bias for happy, angry and fearful facial expressions in a mixed sample using a subliminal face presentation time of 50 ms, Pfabigan et al [44] report a general attentional bias only in men for happy faces under face presentation times of 500 ms. Interestingly, Bar-Haim [55] suggest in a meta-analysis that threat-related stimuli in general do only lead to an attentional bias in clinical samples but not in non-anxious healthy controls. Here we support the idea that neither men nor women show an attentional cueing effect comparing happy to angry faces.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be that subconscious or very short cue presentation times have greater potential to elicit a strong attentional bias and thereby may be more prone to experimental interventions like AND exposure. In this study we decided for the commonly used face presentation time of 500 ms [22, 44, 58, 59] as also in our Stroop task we had opted for a conscious stimulus presentation time of 1000 ms. Taken together we ask to consider our null-results concerning AND-effects on visual cueing only preliminary and urge to include both shorter cue presentation times and eye-tracking in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations